La Violencia familiar relacionada con las conductas disruptivas en los estudiantes de la Unidad Educativa Comunitaria Intercultural Bilingüe “KAWSAY ÑAN” de Gañil: Un enfoque desde Trabajo Social - Becerra Montalván, Santiago Fernando (2025)
Family violence has been a social phenomenon that has persisted throughout history, affecting millions of individuals worldwide. It is most commonly defined as hostility or violent behavior directed towards a family member, resulting in both psychological and social difficulties. In Gañil, an indigenous community in the rural sector of the Saraguro canton, family violence is evident in the family nuclei. Cultural issues, such as customs, traditions, religion and clothing, also contribute to gender differences and ideologies. Family violence has important academic and social consequences on the behavior of children and adolescents of the Intercultural Bilingual Community Education Unit “Kawsay Ñan”. Consequently, this work conducts a correlational study between family violence and disruptive behaviors, revealing that physical violence, psychological violence and sexual coercion are the most frequent types of violence, and that as aggressiveness in the home increases, so does in the educational institution.